Karakteristik Fisikokimia dan Sensoris Selai Bengkuang (Pachyrhizus Erosus L.) dengan Penambahan Pektin dan Asam Sitrat pada Berbagai Konsentrasi - Santosa, Arif Prashadi; Hajoeningtijas, Oetami Dwi; Noviandita, Ismi (Proceedings Series on Physical & Formal Sciences, 2021)
This research aimed to figure out the effect of differences in concentration of citric acidand pectin and their interactions on the content of proximate and sensory of jam.The research was conducted using a completely randomized design (CRD) with a factorial pattern consisting of two factors.The first factor was the comparison of thethree levels of citric acid (A) concentration:1% (A1), 2% (A2),and 3% (A3) of the total ingredients for making jam.The second factor was pectin concentration (P) in 4 levels: 0.83%(P1), 1.0% (P2), 1.17% (P3), and 1.34% (P4) of the total ingredients for making jam.The chemical parameters tested included moisture content, fiber content, ash content, and antioxidant, while the physical parameters included pH and viscosity.The sensory test assessments includedaroma, taste, color, preference, and spreadability.The results indicated that the comparison of the concentration of citric acid (A) had a significant effect on the proximate analysis of the pH variable; however, it had no significant effect on several other variables:moisture content, crude fiber content, ash content, viscosity, and antioxidant.The results of the sensory test did not significantly affect the variables of aroma, taste, color, preference, and spreadability.In addition, the treatment of pectin (P)concentration ratio had a significant effect toward proximate analysis on water content and viscosity variable, but it had no significant effect on the variables offiber content, ash content, pH, and antioxidant.Meanwhile, the sensory test had a significant effect on the preference variable and had no significant effect on the aroma, taste, color, and spreadibilityvariables.The treatment interactions (AxP) significantly affectedproximate analysis on pH and viscosity variables.However, it did not affect the variable of water content, fiber content, ash content, and antioxidantsignificantly.The sensory test results hada significant effect onpreference variable.The best treatment wason the use of 1% citric acid concentration and 0.83% pectin concentration (A1P1) with 42.63% water content, 37.54% fiber content, 0.25% ash content, pH of 3.30, a viscosity of 8.49 cP, and an antioxidant of 9.22%.The treatment resulted in the aroma of 3.67 (delicious), taste of 4.67 (delicious), color of 4.00 (yellowish white), preference of 5.00 (likevery much), and spreadability 3.67 (easy).